1998
DOI: 10.1124/mol.53.1.128
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Seventh Transmembrane Region in High Affinity Binding of a β2-Selective Agonist TA-2005

Abstract: To determine the structural basis for binding subtype selective agonists in the beta-adrenergic receptor (beta AR), we examined the interaction of the mutant beta 2AR and chimeric beta 1/beta 2AR with a selective beta 2AR agonist, TA-2005 (8-hydroxy-5-[(1R)-1-hydroxy-2-[N-[(1R)-2-(p-methoxyphenyl)-1-methyle thy l] amino]ethyl] carbostyril hydrochloride). The beta 2AR mutant with Ala substituted for Ser204 (S204A) significantly decreased the affinities for TA-2005, des-8-hydroxy-TA-2005 derivative (compound I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 33 publications
(28 reference statements)
10
68
0
2
Order By: Relevance
“…Thus, the third intracellular loop and the C terminus of ␤-ARs are not essentially involved in ligand binding, although those domains play important roles in interacting with G proteins and adenylyl cyclase (O'Dowd et al, 1988;Green et al, 1992). This is consistent with previous reports that the binding domain of ␤-ARs is mainly located in a pocket in the transmembrane domains 3, 5, and 6 (Dixon et al, 1987;Dohlman et al, 1988;Wong et al, 1988;Hockerman et al, 1996) and that other transmembrane domains, such as 2, 6, and 7, may also play a role in determining ␤-AR subtype-selectivity for antagonists (Marullo et al, 1990;Kurose et al, 1998;Isogaya et al, 1998Isogaya et al, , 1999Kikkawa et al, 1998). Thus, the inhibitory effects of ICI 118,551 on the chimera-induced elevations of myocyte contraction and cAMP production is mediated by its inverse agonist functionality, rather than by enhanced binding affinity of ICI 118,551 to those chimeras.…”
Section: The Third Intracellular Loop and The C Terminussupporting
confidence: 82%
“…Thus, the third intracellular loop and the C terminus of ␤-ARs are not essentially involved in ligand binding, although those domains play important roles in interacting with G proteins and adenylyl cyclase (O'Dowd et al, 1988;Green et al, 1992). This is consistent with previous reports that the binding domain of ␤-ARs is mainly located in a pocket in the transmembrane domains 3, 5, and 6 (Dixon et al, 1987;Dohlman et al, 1988;Wong et al, 1988;Hockerman et al, 1996) and that other transmembrane domains, such as 2, 6, and 7, may also play a role in determining ␤-AR subtype-selectivity for antagonists (Marullo et al, 1990;Kurose et al, 1998;Isogaya et al, 1998Isogaya et al, , 1999Kikkawa et al, 1998). Thus, the inhibitory effects of ICI 118,551 on the chimera-induced elevations of myocyte contraction and cAMP production is mediated by its inverse agonist functionality, rather than by enhanced binding affinity of ICI 118,551 to those chimeras.…”
Section: The Third Intracellular Loop and The C Terminussupporting
confidence: 82%
“…We have studied the binding domains for ␤ 1 -and ␤ 2 -selective agonists and have reported that transmembrane domains 2 and 7 of ␤ 1 -and ␤ 2 -adrenergic receptors form a binding pocket, and that Leu 110 , Thr 117 , and Val 120 in transmembrane domain 2 of ␤ 1 -adrenergic receptor or Tyr 308 in transmembrane domain 7 of ␤ 2 -adrenergic receptor are major determinants for ␤ 1 -or ␤ 2 -selective agonists, respectively (Isogaya et al, , 1999Kikkawa et al, 1998). However, ␤ 1 -selectivity of T-0509 and denopamine [K i (␤ 2 )/K i (␤ 1 )] used in the previous study was at most 10-fold.…”
Section: Leumentioning
confidence: 99%
“…Кармотерол ведет себя как очень сильный и се лективный агонист β2 АР, обладает в 53 раза бóльшей аффинностью в отношении β 2 АР по сравнению с β 1 АР [44] и приблизительно в 5 раз более селекти вен в отношении β 2 АР, присутствующих в препара те трахеи, чем в тех, которые регулируют хронотроп ный ответ в правом предсердии [45]. В результате воздействия кармотерола продемонстрирована наи большая мощность среди всех LABA при оценке на гладких мышцах трахей морских свинок, сокращен ных под воздействием метахолина [44].…”
Section: новое о лекарственных препаратахunclassified
“…Длительность расслабления глад кой мускулатуры трахеи под воздействием кармо терола была более длительной по сравнению с формотеролом и салметеролом [44]. Кроме того, в экспериментальных условиях in vivo и in vitro про демонстрированы быстрое начало и длительность действия препарата [45].…”
Section: новое о лекарственных препаратахunclassified